Paul Ricoeur and with a good and other life other: a purpose of teamwork in health - Rapimán Salazar, María Eugenia; Acevedo Pérez, Irene Alicia; Osorio Ulloa, Mauricio Adrián; Torres Canales, Adrián Darío (Acta Bioethica, 2020)
This article essential aspects of teamwork in the field of health, are reviewed from the ethical perspective of Paul Ricoeur. Ethics conceptualized by the author as “tending to a good life with others and for others in just institutions”, is an alternative for reflection, analysis and discussion the ethical foundation of teamwork in health, and urges its members to build and / or redesign the bases for the articulation and implementation of this intentionality of good life with others and others in their daily lives. Teamwork is an instance in which the human being in intersubjectivity with others, develops his way of being ethical and moral constructs his experience. To the extent that each member develop and exercise permanent interpretation of himself and his actions leading the esteem and their self-esteem, may help establish better living spaces and working with others.